A novel computing approach for third order boundary layer - Equation Yasir Khan; Zdeněk Smarda (Universiti Kebangsaan Malaysia, 2012)
This paper proposed an efficient modification of homotopy perturbation transform method (HPTM), namely modified homotopy perturbation transform method (MHPTM) for the solution of third order boundary layer equation on semi-infinite domain. The technique was based on the application of Laplace transform to boundary layers in fluid mechanics. The nonlinear terms can be easily handled by the use of He’s polynomials. The Pade´ approximants, that often show superior performance over series approximations, were effectively used in the analysis to capture the essential behavior of the boundary layer equation on infinity. We then conduct a comparative study between the MHPTM and the existing results with the help of third order boundary layer equation. The results obtained indicated that the MHPTM was effective and promising.